Daily life stressors and coping strategies during widowhood: A diary study after one year of bereavement. Issue 8 (13th September 2016) - Ryckebosch-Dayez, Anne-Sophie; Zech, Emmanuelle; Mac Cord, Jordan; Taverne, Cédric
ABSTRACT: The present study examined the frequency and types of bereavement-related stressors and coping strategies that 40 widowed people encountered and reported in a diary over the course of 1 week. The results indicated that, after 1 year of bereavement, (a) the most frequent stressors were oriented to the loss of the spouse, (b) specific coping strategies were used and found effective to deal with specific types of stressors, (c) stressors were sometimes dealt with using several successive strategies or no strategy at all, and (d) clusters of stressors and strategies were associated with specific moments of appearance during the day.